A Framework for Accounting Theory - BAIT-ELMAL, MOHAMED (Dirasat in Economics and Business, 1980)
Accounting was first originated to serve society. By society the writer means the environment surrounding the accounting profession; i.e. the management, investors, stockholders and the creditors, etc. When the accounting profession started, it served the function of describing only what had been done; accounting was then a study of methods, not causes.